2015
DOI: 10.1118/1.4906183
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge‐based prediction of plan quality metrics in intracranial stereotactic radiosurgery

Abstract: The results demonstrate the ability to predict SRS QMs precisely and to identify suboptimal plans. Furthermore, the knowledge-based DVH predictions were directly used as target optimization objectives and allowed a standardized planning process that bettered the clinically approved plans. Full clinical application of this methodology can improve consistency of SRS plan quality in a wide range of PTV volume and proximity to OARs and facilitate automated treatment planning for this critical treatment site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
109
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(111 citation statements)
references
References 21 publications
1
109
1
Order By: Relevance
“…A large and rather mature IMRT plan dataset was required to effectively guide VMAT planning. In most recent studies [24,25] a comprehensive knowledge-based method was used for predicting achievable dose-volume histograms (DVHs) to standardize and improve treatment planning. [25] Tol et al evaluated the method for head and neck cancer using a library of different patient plans to make a model that can predict achievable DVHs for defining optimization objectives for new patients.…”
Section: Discussionmentioning
confidence: 99%
“…A large and rather mature IMRT plan dataset was required to effectively guide VMAT planning. In most recent studies [24,25] a comprehensive knowledge-based method was used for predicting achievable dose-volume histograms (DVHs) to standardize and improve treatment planning. [25] Tol et al evaluated the method for head and neck cancer using a library of different patient plans to make a model that can predict achievable DVHs for defining optimization objectives for new patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several publications have reported the feasibility of using RapidPlan to improve OAR sparing (2325) and Jim P. Tol et al (26) showed the potential of using RapidPlan DVH estimation model directly as a plan QC tool for head-and-neck cases. However, these studies built models directly on arbitrary training plans with no special selection criteria, which could influence the performance of the RapidPlan DVH estimation models (3,17). Moreover, none of these works have systematically investigated the influence of using different mix of optimization objectives and priorities for multiple OARs and PTVs.…”
Section: Discussionmentioning
confidence: 99%
“…Since the results that the model produces are roughly dependent on the mean quality of the training plans(18), a strategy to identify high quality plans for a refined training set for each OAR is critical(3,17). We decided to select the top 30 (~1/3 of the entire sample) plans with an apparent emphasis on PBM or bowel sparing to generate refined training sets for these models, since these are principal OARs for the protocol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These steps can range from the estimation of field direction,1 weights of optimization objectives,2 and even dose distribution 3, 4. The majority of KBP work, however, has focused on estimating dose–volume histograms (DVHs)5, 6, 7, 8, 9 which are commonly used to evaluate plan quality and guide the inverse planning process.…”
Section: Introductionmentioning
confidence: 99%